Acute diquat poisoning induces paralytic ileus and hepatic portal venous gas: a case report - Hongji Yin; Dongxing Sun; Fengting Liu; Ruosai Xin (Frontiers in Toxicology)
Diquat is a non-selective, broad-spectrum herbicide. Although its toxicity is significantly lower than paraquat, it still has a high mortality rate when ingested in large quantities. This report presents the case of a 21-year-old female who developed severe paralytic ileus and the rare radiological finding of hepatic portal venous gas (HPVG) after ingesting 150 mL of diquat. Despite aggressive treatment, including gastric lavage, drainage, and blood purification, the patient ultimately succumbed to multiple organ failure. This report explores the potential causes of HPVG, including infection and elevated intestinal pressure, and highlights the possibility that montmorillonite may have exacerbated this process.